HUBUNGAN USIA DENGAN PENINGKATAN TEKANAN DARAH POST HEMODIALISA PADA LANSIA DI RUMAH SAKIT IHC LAVALETTE KOTA MALANG - Taufan Arif; Anggy Dwi Pramesty; Joko Wiyono; Sulastyawati Sulastyawati (Jurnal Keperawatan Terapan, 2024)
Abstract: While undergoing hemodialysis therapy, patients experience health problems, including hemodynamic disorders, which are a common problem. Factors that cause changes in post-hemodialysis blood pressure can be caused by age. Elderly patients undergoing hemodialysis treatment experience an increase in blood pressure after hemodialysis by 80%. A possible factor causing an increase in post-hemodialysis blood pressure is age. The aim of this study was to determine the relationship between age and increased post-hemodialysis blood pressure. The research design uses a "cross-sectional" approach. The sampling method used "purposive sampling" with 74 elderly people. Determination of respondents was based on the inclusion criteria of patients who experienced an increase in blood pressure after hemodialysis, and patients who routinely underwent hemodialysis therapy. Test data analysis using univariate analysis to determine the characteristics of respondents. Bivariate analysis used the Spearman rank test for the age variable which was associated with an increase in post-hemodialysis blood pressure. Age bivariate test with p-value 0.001. Age is associated with an increase in post-hemodialysis blood pressure. Keywords: Blood pressure, hemodialysis, elderly, ESRD